Está en la página 1de 22

Introduction:

The Z-Transform plays an important role in the field of Communication


Engineering and Control Engineering at the stage of analysis and representation
of discrete-time linear shift invariance system. When continuous signals are
sampled, discrete-time functions arise. The application of Z-transform in discrete
time systems is similar to that of Laplace transform in continuous time systems.

Definition of the Z-Transform:
Let ( ) { } n f be a sequence defined for all positive integers n.
Then, the Z-transform of f(n) is defined as
{ } ) z ( F z ) n ( f ) n ( f Z
n
0 n
= =

, (i)
where z is an arbitrary complex number.
This is one-sided Z-transform.
1 11 1
st st st st
Topic Topic Topic Topic
Z ZZ Z- -- -Transforms Transforms Transforms Transforms
Introduction
Definition of the Z-Transform
Properties of Z-Transforms
Z-Transforms of basic sequences
Z-Transforms of standard discrete functions
First shifting theorem, second shifting theorem
Two basic theorems
(Initial value theorem and Final value theorem)
Convolution theorem
Prepared by:
Dr. Sunil
NIT Hamirpur (HP)
(Last updated on 13-11-2007)
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 2
Remarks:
1. If ( ) { } n f is defined for .. ,......... 2 , 1 , 0 n = then ( ) { } ( )
n
n
z n f n f Z

= and is
called two sided Z-transform.
2. If ( ) 0 n f = for n < 0 then {f(n)} is called a casual sequence.
3. The bracket {} represents sequence.
The infinite series on RHS of (i) will convergent only for certain values of z
depending on the sequence f(n).
The inverse Z-transform of Z{f(n)} = F(z) is defined as ( ) { } ). n ( f z F Z
1
=



Z-Transform for discrete values of t:
If f(n) is a function defined for discrete values of t, where t = nT, n = 0, 1, 2, ..,
T being the sampling period, then Z-transform of f(t) is defined as
{ } ) z ( F z ) nT ( f ) n ( f Z
n
0 n
= =

.
Note: The important element of discrete-time systems is the samples in which a switch
close to admit an input signal in every T seconds. A samples is a conversion device
which converts a continuous signal into a sequence of pulses occurring at sampling
instants 0, T, 2T, , where T is the sampling period.
Convergence of series (Region of convergence):
Consider { }
n
0 n
z ) n ( f ) n ( f Z

= .
Here
n
n
z ) n ( f u

= , then
n
1 n
n u
u
Lt
+


( )
( )
( )
n
1 n 1
n
z n f
z 1 n f
Lt

+

+ ( )
( )
1
n
z
n f
1 n f
Lt


+
= .
Remember: If a series of the form ... x a ...... x a x a a x a
n
n
2
2 1 0
0 n
n
n
+ + + + + =

=
(i)
is given, then, in the power series (i),
n
n n
x a u = and
1 n
1 n 1 n
x a u
+
+ +
=
x .
a
a
Lim
x a
x a
Lim
u
u
Lim
n
1 n
n
n
n
1 n
1 n
n
n
1 n
n
|
|

\
|
= =
+

+
+

+

.
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 3
If l =
|
|

\
|
+

n
1 n
n a
a
Lim , then by DAlemberts ratio test,
the series converges, when x l is numerically less than 1. i.e. when
l
1
x < and diverges
for all other values.
Thus, by ratio test, the series is convergent if
( )
( )
z
z f
1 n f
Lt
n
<
+

.
The region of convergence is the exterior of the radius R (say).
Hence, R is called the radius of convergence of the series ( )
n
0 n
z n f

.
Important Note: While finding Z-transforms
(i). if f(n) is given, then simply replace f(n).
(ii). if f(t) is given, then replace t by nT.

Properties of Z-Transforms:
Linear property:
Statement: If a, b, c, be any constants and u
n
, v
n
, w
n
be any discrete functions, then
( ) ( ) ( ) ( )
n n n n n n
w cZ v bZ u aZ cw bv au Z + = + .
This means that Z-transform is linear.
Proof: Now since ( ) ( )
n
n n n
0 n
n n n
z cw bv au cw bv au Z

=
+ = +

(by definition)

n
n
0 n
n
n
0 n
n
n
0 n
z w c z v b z u a

=

+ =
( ) ( ) ( )
n n n
w cZ v bZ u aZ + = .
Change of scale (or damping rule):
If ( ) z U ) v ( Z
n
= , then ( ) az U ) v a ( Z
n
n
=

.
Proof: Since ( ) ( ) az U az . u z . u a ) v a ( Z
n
n
0 n
n
n
n
0 n
n
n
= = =


.
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 4
Corollary: ( )
|

\
|
=
a
z
U u a Z
n
n
.
Observation: (Reason behind the name damping rule)
The geometric function
n
a

when 1 a < , damps the function u


n
, hence the name
damping rule.
Multiplication by n:
If ( ) ) z ( u u Z
n
= , then ( )
( )
dz
s dU
z nu Z
n
= .
Proof: Here ( ) ( ) ( )
n
n
0 n
1 n
n
0 n
n
n
0 n
n
z
dz
d
u z z n u z z u . n nu Z

=

= = = .
( ) ( ) z U
dz
d
z z u
dz
d
z z u
dz
d
n
n
0 n
n
n
=
|
|

\
|
= =


.
Extension: By mathematical induction, we obtain ( ) ( )
( )
m
m
m
n
m
dz
z U a
z u n Z = .
Shift property:
If f(n) is a casual sequence and m is any positive integer, then
( ) { } ( ) z F z m n f Z
m
= , where ( ) ( ) { } n f Z z F = .
Proof: Since ( ) { } ( )
n
0 n
z m n f m n f Z

=
=


( )
( )
( ) ( ) x F z z . z k f z k f
m m k
0 k
k m
m k

=
+

=
= = =


( ) { } ) z ( F z m n f Z
m
= .
Corollary: ( ) [ ] ( ) { }
m n n
1 m 1
n F Z ) m n ( f z F z Z


= = .

Z-Transform of basic sequences:
1. Prove that
1 z
kz
) k ( Z

= , if 1 z >
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 5
Proof: ( ) { }
1 z
kz
z 1
1
k ........ z z 1 k kz k Z
1
2 1 n
0 n

=

= + + + + = =

, if 1 z > .
Particular case: When k = 1, then ( )
1 z
z
1 Z

= , if 1 z > .
2. Prove that ( ) { }
1 z
z
1 Z
n
+
= , if 1 z >
Proof: ( ) { } ( )
n n
0 n
n
z 1 1 Z

=
=

( )
1 z
z
z
1
1
1
z
n
0 n
+
=
+
= =

=
, if 1 z > .
3. Prove that { }
a z
z
a Z
n

= , if a z > .
Proof: { }
a z
z
z
a
1
1
z
a
z a a Z
n
0 n
n n
0 n
n

= |

\
|
= =


=

=
if a z > .
4. Prove that { }
( )
2
1 z
z
n Z

= .
Proof: ( ) ( ) { }
( )
2
n
0 n
1 z
z
1 z
z
dz
d
z 1 Z
dz
d
z z n

= |

\
|

= =

.
5. Prove that { }
( )
2
n
a z
az
na Z

= .
Proof: { }
( )
2
n
a z
az
a z
z
dz
d
z na Z

=
)
`

= .
Note: ( ) ( ) ( ) n z
dz
d
z n Z
m
m 1 m
=
+
.
6. Prove that { }
( )
1 cos z 2 z
cos z z
n cos Z
2
+

= ; { }
1 cos z 2 z
sin z
n sin Z
2
+

= if 1 z > .
Proof: We know that { }
a z
z
a Z
n

= , if a z > .
Let

=
i
e a { }
{ } +
=

sin i cos z
z
e z
z
e Z
i
in
.
{ }
{ }
{ }{ } +
+
= +
sin i cos z sin i cos z
sin i cos z z
n sin i n cos Z
( )
1 cos z 2 z
sin iz cos z z
2
+
+
= .
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 6
Equating real and imaginary parts, we get
{ }
( )
1 cos z 2 z
cos z z
n cos Z
2
+

= ; { }
1 cos z 2 z
sin z
n sin Z
2
+

= ; 1 z > .
7. Prove that { }
( )
2 2
n
r cos zr 2 z
cos r z z
n cos r Z
+

= and
{ }
2 2
n
r cos zr 2 z
sin zr
n sin r Z
+

= , if r z > .
Proof: { }
a z
z
a Z
n

= if a z > .
Let

=
i
re a in { }
n
a Z { }

=
i
in n
re z
z
e r Z .
( ) { }
+
(

\
|
(

+ |

\
|
|

\
|
=

\
|
|

\
|
= +

2
2
i
n
sin cos
r
z
sin i cos
r
z
r
z
e
r
z
r
z
n sin i n cos r Z .
Equating real and imaginary parts, we get
{ }
( )
2 2
n
r cos zr 2 z
cos r z z
n cos r Z
+

= and { }
2 2
n
r cos zr 2 z
sin zr
n sin r Z
+

= , if r z > .

Z-Transform of standard discrete functions:
1. Prove that ( )
( )
2
1 z
Tz
t Z

= .
Proof: ( ) ( ) ( ) ) 1 ( Z
dz
d
z T nz T z nT t Z
n
0 n
n
0 n
= = =

=



( )
2
1 z
Tz
1 z
z
dz
d
Tz

= |

\
|

= .
2. Prove that (i) ( )
aT
at
e z
z
e Z

= ,
aT
e z

> ;
(ii) ( )
aT
at
e z
z
e Z

= ,
aT
e z > .
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 7
Proof: (i) ( ) ( )
atT
n
n
aT
0 n
n anT
0 n
at
e z
z
z e z e e Z

= = =

, provided
aT
e z

> .
(ii) ( ) ( )
atT
n
n
aT
0 n
n anT
0 n
at
e z
z
z e z e e Z

= = =

=

, provided
aT
e z > .
3. Prove that ( )
( )
1 T cos z 2 z
t cos z z
t cos Z
2
+

= .
Proof: ( ) ( ) = =

n cos Z Tz n cos t cos Z


n
, where T =

( )
1 T cos z 2 z
T cos z z
2
+

= .
Aliter:
( )
(
(

+
=

2
e e
Z t cos Z
t i t i
(

=
T i T i
e z
z
e z
z
2
1 ( )
( )( )(
(


+
=


T i T i
T i T i
e z e z
e e z 2
2
z


( ) (
(

+ +

=

1 z e e z
T cos 2 z 2
2
z
T i T i 2
( )
1 T cos z 2 z
T cos z z
2
+

= .
4. Prove that ( )
1 T cos z 2 z
T sin z
t sin Z
2
+

= .
Proof: ( )
(
(


=

2
e e
Z t sin Z
t i t i
(

=
T i T i
e z
z
e z
z
i 2
1


( ) (
(

+ +

=


1 e e z z
e e
i 2
z
T i T i 2
T i T i

1 T cos z 2 z
T sin z
2
+

= .
5. Prove that ( ) ( ) { }
1 k k
t Z
dz
d
Tz t Z

= .
Proof: ( ) ( )
( ) 1 n 1 k k
0 n
1 k
0 n
k
z T n Tz z nT t Z
+

=

= = ( )
( ) 1 n 1 k
0 n
nz nT Tz
+

= (i)
Similarly, ( ) ( )
n 1 k
0 n
1 k
nz nT t Z

= .
( ) [ ] ( )
( ) 1 n
0 n
1 k
z n t Z
dz
d
+

=

( )
1 n 1 k
0 n
nz z nT
+

= . (ii)
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 8
Using (ii) in (i), we get ( ) ( ) [ ]
1 k k
t Z
dz
d
Tz t Z

= . (iii)
Setting k = 1, 2, 3, .. we get ( ) ( ) . ,......... t Z , t Z
2

( ) ( ) [ ]
( )
2
1 z
Tz
1 z
z
dz
d
Tz 1 Z
dz
d
Tz t Z

= |

\
|

= = , (iv)
( )
( )
( )
( )
3
2
2
2
1 z
1 z z T
1 z
Tz
dz
d
Tz ) t ( z
dz
d
Tz t Z

+
=
|
|

\
|

= = , (v)
and so on.
FIRST SHIFTING THEOREM:
Statement: If ( ) { } ( ) z F t f Z = then ( ) { } { }
aT at
ze F t f e Z =

.
Proof: { } ( ) ( )( )
n
aT
0 n
n ant
0 n
at
ze nT f z nT f e ) t ( f e Z


= =
{ }
aT
ze F = ( )
(
(

n
0 n
z nT f ) z ( F Q
Thus ( ) { } ( ) { } aT
ze z
at
t f Z t f e Z

= { } z F = , where
aT
ze z .
Deductions of some important results from this theorem:
1. { } { } { } at
ze z
at at
1 z 1 . e Z e Z


= =

aT
ze z
1 z
z

\
|

=
1 ze
ze
aT
aT

= { }
aT
at
e z
z
e Z

=

.
2. { } { } { } at
ze z
at at
t Z t . e Z te Z


= =

( ) aT
ze z
2
1 z
Tz

(
(

=
( )
2
aT
aT
1 ze
Tze

= { }
( )
2
aT
aT
at
e z
Tze
te Z

= .
3. { } { } { } iat
ze z
iat iat
1 Z 1 . e Z e Z


= =

iaT
ze z
1 z
z

\
|

=
iaT
e z
z

=
( )
( )( )
iaT iaT
iat
e z e z
e z z



( ) [ ]
( ) 1 e e z z
aT sin i aT cos z z
iaT iaT 2
+ +
+
=
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 9
{ }
( ) [ ]
1 aT cos z 2 z
aT sin i aT cos z z
e Z
2
iat
+

=


( )
( ) [ ]
1 aT cos z 2 z
aT sin i coaaT z z
at sin t at cos Z
2
+

=
[ ]
( )
1 aT cos z 2 z
aT cos z z
aT cos Z
2
+

= and [ ]
1 aT cos z 2 z
zainaT
aT sin Z
2
+

= .
4. { } { } aT
ze z
at
bt cos Z bt cos e Z

=

( )
bT
ze z
2
1 bT cos z 2 z
bt cos z z

=
{ }
1 bT cos ze 2 e z
bT cos ze ze
aT aT 2 2
aT aT
+

= .
5. { } { } aT
ze z
at
bt sin Z bt sin e Z

=

aT
ze z
2
1 T cos z 2 z
bt sin z

+
=
1 bT cos ze 2 e z
bt sin ze
aT aT 2 2
aT
+
= .

SECOND SHIFTING THEOREM:
Statement: If ( ) { } ) z ( F t f Z = then ( ) { } ( ) ( ) [ ] 0 f z F z T t f Z = + .
Proof: Since ( ) { } ( )
n
0 n
z T nT f T t f Z

=
+ = +


( ) [ ]
( ) 1 n
0 n
z T 1 n f z
+

=
+ =

( )
k
1 k
z kT f z

=
( ) ( ) ( ) [ ] ) 0 ( f z F z 0 f z kT f z
k
0 k
=
(
(

.
TWO BASIC THEOREMS
Initial value theorem: If ( ) { } ( ) z F t f z = then ( ) ) z ( f Lt 0 f
z
= .
Proof: ( ) { } ( )
n
0 n
z nT f t f Z ) z ( F

= =
( )
( ) ( )
+ + + = ...... ..........
z
T . 2 f
z
T . 1 f
T . 0 f
2
( ) ( ) ( ) + + + ........ T 2 f
z
1
T f
z
1
0 f
2

( ) ) 0 ( f z F Lt
z
=

.
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 10
Final value theorem: If ( ) [ ] ( ) z F t f Z = then ( ) ) z ( F 1 z Lt ) t ( f Lt
1 z z
=

.
Proof: ( ) [ ] ( ) [ ]
n
0 n
z ) nT ( f T nT f ) t ( f T t f

=
+ = +


( ) ( ) [ ]
n
0 n
z ) nT ( f T nT f ) z ( F ) 0 ( zf z zF

=
+ =


( ) [ ] ( ) { }
(
(

+ =

=


n
0 n
1 x 1 x
z ) nT ( f T nT f Lt ) 0 ( zf z F ) 1 z ( Lt
[ ] ( ) { } ) nT ( f T nT f ) 0 ( f ) z ( F ) 1 z ( Lt
0 n
1 x
+ =


( ) { } [ ] ) nT ( f T 1 n f ..... ) T ( f ) T 2 ( f ) 0 ( f ) T ( f Lt
n
+ + + + =


{ } ( ) ) 0 ( f ) t ( f Lt ) 0 ( f f ) 0 ( f T ) 1 n ( f Lt
t n
= = + =


( ) ( ) t f Lt ) z ( F 1 z Lt
t 1 z
= .
Now let us find Z-transform of various types of sequences:

Q.No.1.: Find the Z-transform of
(i)
2
n , (ii) ( ) 1 n n , (iii)
n
1
,
(iv)
( ) 1 n n
1
+
, (v)
2
n
cos

.
Sol.: (i) ( ) ( ) ( )
( )
( )
( )
3 2
2
1 z
1 z z
1 z
z
dz
d
n z
dz
d
n . n Z n Z

+
=

= = = . Ans.
(ii) ( ) { } { } ( ) ( ) n Z n Z n n Z 1 n n Z
2 2
= =

( )
( ) ( )
( )
( ) ( )
3 3
2
3 3
1 z
z 2
1 z
1 z z z z
1 z
z
1 z
1 z z

+
=

+
= . Ans.
(iii) |

\
|
= + + + = =
)
`

z
1
1 log .........
z 3
1
z 2
1
z
1
z
n
1
n
1
Z
3 2
n
1 n
, if 1
z
1
< |

\
|


|

\
|

=
1 z
z
log , if 1 z > .
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 11
(iv)
( )
)
`

)
`

=
)
`

+
=
)
`

+ 1 n
1
Z
n
1
z
1 n
1
n
1
Z
1 n n
1
Z

n
1 n
n
1 n
z
1 n
1
z
n
1

=
+
=



)
`

+ + + |

\
|

= .... ..........
z 3
1
z 2
1
1
1 z
z
log
2

+ |

\
|
+ |

\
|
+ |

\
|

= . ..........
z
1
3
1
z
1
2
1
z
1
z
1 z
z
log
3 2

( )
)
`


=
)
`

\
|
|

\
|

=
z
1 z
log 1 z
z
1
1 log z
1 z
z
log . Ans.
(v) + =

=
)
`

........ ..........
x
1
z
1
1 z
2
n
cos
2
n
cos Z
4 2
n
0 n


1 z
z
z
1
1
2
2
1
2
+
=
(

+ =

, if 1 z > . Ans.
Q.No.2.: Find the Z-transform of
(i) ( ) ) 2 n ( 1 n
2
1
+ + , (ii) ( ) 0 b , 0 a ab
n
,
(iii)

=
=
k n ; 0
k n ; 1
) n ( f , (v)

>
=
0 n if 1
0 n if 0
) n ( f ,
(vi)

=
otherwise 0,
0 n ,
! n
a
) n ( f
n
.
Sol.: (i) ( )( ) ( ) ( ) ( ) { } 1 Z 2 n Z 3 n Z
2
1
2 n 1 n
2
1
Z
2
+ + =
)
`

+ +

( )
( ) ( )
( )
(
(

+
=
1 z
z 2
1 z
z 3
1 z
1 z z
2
1
2 3
, if 1 z > . Ans.
(ii) { } ( )
n
0 n
n n
0 n
n n
z
b
a z b a b aZ ab Z |

\
|
= = =


=

=
b z
az
b z
z
a

=
)
`

= , if b . z > . Ans.
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 12
(iii) ( ) { } ( ) + + + = = =

=

.........
z
3
z
2
z
1
nz n f n f Z
3 2
n z
0 n
n
0 n


( )
2
2
1 z
z
z
1
1
z
1

= |

\
|
=

, if 1 z > . Ans.
(iv) ( ) { } ( ) ( )
k
k n
k n
0 n 0 n
z
1
z . z . 0 z n f n f Z
n
= + = =

=


. Ans.
(v) { } ( )
z 1
1
z z 1 z ) n ( f ) n ( f Z
n
0 n
n
n
n
n

= = = =


=

=
, if 1 z < . Ans.
(vi) ( ) { } ( )
( )
z / a az
n
1
0 n
n
n
0 n
n
0 n
e e
! n
az
z
! n
a
z n f n f Z
1
= = = = =

=

. Ans.
Q.No.3.: Find the Z-transform of
(i). ( ) 1 n u (ii) ( ) 1 n 4
n
(iii). ( ) k n .
Sol.: (i) ( ) { }
n
1 n
z . 1 1 n u Z

=
)
`

+ + + = + + + = . ..........
z
1
z
1
1
z
1
........
z
1
z
1
z
1
2 3 2

=
z
1
1
1
z
1
if 1
z
1
<
1 z
1

= , if 1 z > . Ans.
(ii) ( ) { } ( )
z
4
z 1 n 4 1 n 4 Z
n n
0 n
n
= =

. Ans.
(iii) ( ) { } ( )
k
n
0 n
z
1
z k n k n Z = =

, k is a positive integer. Ans.


Q.No.4.: Find the Z-transform of
(i)
2 t
t e

, (ii)
3 t 2
t e

, (iii)
5 t 2
e
+
,
(iv) t 2 sin e
t 3
, (v) t cos e
t 4
, (vi) n cos a
n
.
Sol.: (i) [ ] { } T
ze z
2 2 t
t Z t e Z

=
( )
( )
( )
( )
3
T
T T 2
ze z
3
2
1 ze
1 ze ze T
1 z
1 z z T
T

+
=

+
=

. Ans.
(ii) [ ] { } T 2
ze z
3 3 t 2
t Z t e Z

=
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 13

( )
( )
( )
( )
4
T 2
t 4 2 T 2 T 2 3
ze z
4
2 3
1 ze
e z ze 4 1 ze T
1 z
z z 4 1 z T
T 2

+ +
=

+ +
=

. Ans.
(iii) { } { }
T 2
5 t 2 5 5 t 2
e z
z
. e e Z e e Z

= =
+
. Ans.
(iv) { } { } t 3
ze z
t 3
t 2 sin Z t 2 sin e Z

=
t 3
ze z
2
1 T 2 cos z 2 z
T 2 sin z

+
=

1 T 2 cos ze 2 e z
T 2 sin ze
t 3 T 6 2
t 3
+
=

. Ans.
(v) { } { } t 4
ze z
t 4
t cos Z t cos e Z

=
( )
t 4
ze z
2
1 T cos z 2 z
T cos z z

=

( )
1 T cos ze 2 e z
T cos ze ze
t 4 T 8 2
t 4 t 4
+

=


. Ans.
(vi) ( )
n n
0 n
n
z . n cos a n cos a Z

=
=



1 3 2
z
a
1 . ..........
z
a
z
a
z
a
1

\
|
+ = +
|

\
|

\
|
+ = if 1
z
a
<

a z
z
+
= , if a z < . Ans.
Q.No.5.: If
( )
1 aT cos z 2 z
aT cos z z
) z ( F
2
+

= , find f(0).
Sol.: From initial value theorem, ( ) ( ) z F Lt 0 f
z
= .
Initial value theorem: If ( ) { } ( ) z F t f z = , then ( ) ) z ( f Lt 0 f
z
= .
( )
( )
1
1 aT cos z 2 z
aT cos z z
Lt 0 f
2
z
=
+

=

. (by L-Hospital rule)
Q.No.6.: If ( )
T
e z
z
z F

= , find ( ) t f Lt
t
.
Sol.: From final value theorem,
Initial value theorem: If ( ) { } ( ) z F t f z = , then ( ) ) z ( f Lt 0 f
z
= .

Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 14
we have ( ) ( ) ( ) ( ) 0
e z
z
1 z Lt z F 1 z Lt t f Lt
T
1 z 1 z t
=

= =


.
Q.No.7.: Find the Z-transform of
(i) ) T t sin( + , (ii)
( ) T t 2
e
+
, (iii) ( )
( ) T t
e T t
+
+ .
Sol.: (i) ( ) { } ( ) { } T t f Z T t sin Z + = + where ( ) t sin t f =
{ }
(


+
= = 0
1 T cos z 2 z
T sin z
z ) 0 ( f ) z ( F z
2
1 T cos z 2 z
T sin z
2
2
+
= . Ans.
Aliter: ( ) { } { } T sin t cos T cos t sin Z T t sin Z + = +
( ) ( ) t cos Z . T sin t sin Z . T cos + =

( )
)
`

+
)
`

+
=
1 T cos z 2 z
T cos z z
1 T cos z 2 z
T sin z
T cos
2 2


1 T cos z 2 z
T sin z
2
2
+
= . Ans.
(ii) { } ( ) { } T t f Z e Z
) T t ( 2
+ =
+
, where ( )
t 2
e t f =
SECOND SHIFTING THEOREM:
Statement: If ( ) { } ) z ( F t f Z = then ( ) { } ( ) ( ) [ ] 0 f z F z T t f Z = + .
( ) [ ]
(

= = 1
e z
z
z ) 0 ( f z F z
T 2


T 2
T 2
e z
ze

= . Ans.
Aliter:
( )
{ } { }
T 2
T 2 t 2 T 2 T t 2
e z
z
. e e Z e e Z

= =
+
. Ans.
(iii) ( )
( )
[ ] ( ) { }
t T T t
e T t Z e e T t Z
+
+ = + ( ) ( ) [ ]
t t T
e TZ te Z e

+ =

( )
(
(

=
T 2
T
T
T
e z
Tz
1 ze
Tze
e
( )
(
(

=

1 ze
z Te
1 ze
Tze
e
T
T
2
T
T
T


( ) ( )
2
T
T 2
2
T
T
T T
1 ze
e Tz
1 ze
ze
Tze . e

=
(
(

=

. Ans.
Remember: ( ) [ ] ( ) { }
m n n
1 m 1
n F Z ) m n ( f z F z Z


= = .
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 15
Q.No.8.: Find
)
`

1 z
1
Z
1
given ( )
n 1
1
1 z
z
Z =
)
`

.
Sol.:
)
`

+
=
)
`

+

1 z
z
. z Z
1 z
1
Z
1 1 1

( ) { } ( ) 3,..... 2, 1, n , 1 1
1 z
z
Z
1 n
1 n n
n
1 n n
1
= = =
)
`

+
=



Q.No.9.: Find
)
`

1 z 3
3
Z
1
.
Sol.:
(
(
(
(

=
)
`


3
1
z
z
z Z
3
1
1
1
Z
1 z 3
3
Z
1 1 1 1


1 n
1 n n
1
3
1
3
1
z
z
Z

\
|
=

= ( ) 1 n u
3
1
1 n

\
|


. Ans.
Differentiation:
Let ( ) { } [ ] ) z ( F n f Z = . An infinite series can be differentiated term by term with in
its region of convergence. F(z) may be treated as a function of
1
z

.
( ) ( ) ( )( )
n
1
0 n
n
0 n
z n f z n f z F

=

= = .
Differentiating on both sides w.r.t.
1
z

, we get
( ) ( )( )
1 n
1
0 n
1
z n nf z F
dz
d


= (i)
( ) ( ) { } n nf Z z n nf
dz
) z ( dF
z
n
0 n
1
1
= =

.
( ) { }
1
1
dz
) z ( dF
z n nf Z

= . (ii)
Differentiating (i) w.r.t.
1
z

again, we get
( )
( )
( ) ( )( )
2 n
1
0 n
2
1
2
z n f 1 n n
z d
z F d

=


Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 16
( )
( )
( ) ( ) ( ) { } ) n ( f 1 n n Z z n f 1 n n
z d
z F d
z
n
0 n
2
1
2
2
= =

.
( ) { }
( )
( )
2
1
2
2
z d
z F d
z ) n ( f 1 n n Z

= .
Q.No.1.:Find the Z-transforms of
(i) ) n ( u na
n
, (ii) ( ) ( ) n u a 1 n n
n
.
Sol.: (i) ( ) { } [ ]
1
1
1
1
1
1 n
az 1
dz
d
z
a z
z
dz
d
z n u na Z

= |

\
|

=

( ) ( )
2
1
1
2
1
1
az 1
az
az 1
a
z

= . Ans.
(ii) ( ) ( ) { }
( )
{ }
( )
3
1
2 2
1
1
2
1
2
2 n
az 1
z a 2
az 1
z d
d
z n u a 1 n n Z

= = . Ans.
Note: If a = 1 then ( ) [ ]
( )
2
1
1
z 1
z
n nu Z

= ; ( ) ( ) [ ]
( )
3
1
2
z 1
z 2
n u 1 n n Z

= .
Convolution of sequences:
Definition: The convolution of two sequences {f(n)} and {g}n)} is defined as
( ) ( ) ( ) g * f k n g k f n
k
= =

=
.
Remarks: If it is one sided (right) sequence, take f(k) = 0, g(k) = 0 for k < 0,
then ( ) ( ) ( ) g * f k n g k f n
0 k
= =

=
.
Convolution theorem:
Statement: If w(n) is the convolution of two sequences f(n) and g(n), then
( ) { } { } ( ) { } ) z ( G ). z ( F n g Z . ) n ( f Z ) z ( W n w Z = = =
Proof: ( ) ( ) { }
(
(

= =

=
) k n ( g ) k ( f Z n w Z z W
0 k
( )
n
0 k 0 n
z ) k n ( g k f

=
(
(

=


( )
(
(

=

n
0 n 0 k
z k n g ) k ( f (by changing the order of summation)
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 17
( )
(
(

=
+

=

k p (
0 p 0 k
z p g ) k ( f (Putting p k n = )
( ) ( ) ( ) ( ) z G z F z p g z k f
p
0 p
k
0 k
=
(
(

(
(

=

.
Note: This result will be true only for those values of z inside the region of convergence.
Another form of Convolution Theorem:
Statement: If { } ) z ( F ) t ( f Z = , Z{g(t)} = G(z), then convolution product is
( ) ( ) g * f ) kT nT ( g kT f t w
n
0 k
= =

=

and ( ) { } ( ) ( ) { } ( ) { } ) z ( G ) z ( F t g Z t f Z z W t w Z = = =
Proof: (Here we are dealing with one sided Z-transforms only)
( ) ( )
m
0 m
z mT f z F

= ; ( ) ( )
n
0 m
z nT g z F

=
( ) ( )

=

n
0 n
m
0 m
z nT g z mT f ) z ( G ) z ( F
( )
n m
0 m 0 n
z ) nT ( g mT f

=

= ( ) ( ) { }
n
0 m 0 n
z T p n g pT f

=
|
|

\
|
=


( ) ( ) { } { } g * f Z z T p n g pT f Z
n
0 p
=
|
|

\
|
=

.
Importance: The convolution theorem plays an important role in the solution of
differential equations and in probability problems involving sums of two
independent random variables.
Q.No.1.:Find the Z-transforms of f*g, where
(i) ( ) ) n ( u n f = , ( ) n u 2 ) n ( g
n
= .
(ii) ( ) ( ) n u 3 n f
n
= , ) n ( u 4 ) n ( g
n
= , using convolution theorem.
Sol.: (i) { }
1 z
z
z . 1 ) n ( u Z ) z ( F
n
0 n

= = =

if 1 z >
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 18
( ) { }
2 z
z
z 2 n u 2 Z ) z ( G
n n
0 n
n

= = =

if 2 z >
By Convolution theorem, we get
{ } { } ) z ( G ). z ( F ) z ( W ) n ( w Z g * f Z = = =

( )( ) 2 z 1 z
z
2 z
z
.
1 z
z
2

=

= , if 2 z > .
(ii) ( ) { }
3 z
z
n u 3 Z ) z ( F
n

= = , if 3 z > .
( ) { }
4 z
z
n u 4 Z ) z ( G
n

= = , if 4 z > .
By Convolution theorem, we get
{ } { } ) z ( G ). z ( F ) z ( W ) n ( w Z g * f Z = = =
( )( ) 4 z 3 z
z
4 z
z
.
3 z
z
2

=

= , if 4 z > .
Some useful Z-Transforms:
Z-Transform of sequences:
Sr. No. F(n)
( ) { } n f Z
1 1
1 z
z


2 n
( )
2
1 z
z


3
2
n
( )
3
2
1 z
z z

+

4 3
z
( )
4
2 3
1 z
z z 4 z

+ +

5
( ) 1 n n
( )
2
1 z
z 2


6 ( ) k
n
( )
1 k
1 z
z ! k
+


Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 19
7
( )
n
1
1 z
z
+

8 ) n ( u
1 z
z

, 1 z >
9
( ) 1 n u
1 z
1


10
( ) k n u
1 z
z
. z
k


11
n
1

|

\
|
1 z
z
log , 1 z >
12
1 n
1
+

|

\
|
1 z
z
log z
13
! n
1

z / 1
e
14
( ) n
1
15
( ) k n
k
z


16
) n ( u a
n
or
n
a
a z
z


17
) n ( u na
n
or
n
na
( )
2
a z
az


18
( ) ) n ( u a 1 n
n
+ or ( )
n
a 1 n +
( )
2
2
a z
z


19
) n ( u a ) 1 n ( n
n
or
n
a ) 1 n ( n
( )
3
2
a z
z a 2


20
2
n
cos

or ) n ( u .
2
n
cos


1 z
z
2
2
+

21
2
n
sin

or ) n ( u .
2
n
sin


1 z
z
2
+

22
) n ( u .
2
n
cos a
n

or
2
n
cos a
n


2 2
2
a z
z
+

Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 20
23
) n ( u .
2
n
sin a
n

or
2
n
sin a
n


2 2
a z
az
+

24 ) n ( u . n cos or n cos ( )
1 cos z 2 z
cos z z
2
+


25 ) n ( u . n sin or n sin
1 cos z 2 z
sin z
2
+


26
) n ( u . n cos r
n
or n cos r
n

( )
2 2
r cos zr 2 z
cos r z z
+


27
) n ( u . n sin r
n
or n sin r
n

2 2
r cos zr 2 z
sin rz
+


28
) n ( f a
n

|

\
|
a
z
F
29
( ) n nf
dz
) z ( dF
z
30 1 m
n
+

( ) ( ) n z
dz
d
z
m
m
m


Z-Transform of standard discrete functions:
Sr. No. F(t)
( ) { } t f Z
1 k
t
( ) [ ]
1 k
t Z
dz
d
Tz


2 t
( )
2
1 z
Tz


3 2
t ( )
( )
3
2
1 z
1 z z T

+

4 3
t ( )
( )
4
2 3
1 z
z z 4 1 z T

+

5
( ) t f a
n

|

\
|
a
z
F
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 21
6
( ) ) t ( nf nt nf =
) z ( F
dz
d
z
7 at
e


aT
e z
z

if
aT
e z

>
8 at
e
aT
e z
z

if
aT
e z

>
9 t sin
1 T cos z 2 z
t sin z
2
+

if 1 z >
10 t cos
( )
1 T cos z 2 z
T cos z z
2
+

if 1 z >

*** *** *** *** ***
*** *** ***
***
Home Assignments
Q.No.1.: Find the Z-transforms (One sided) of the following sequences {f(n)}, where f(n)
is
(i) ) n ( u
4
1
n
|

\
|
, (ii) ( ) 3 n , (iii) ( ) ) n ( u 1
n
,
(iv)
2
n
sin 3
n

, (v)
2
n
cos 2
n

, (vi) ( ) 3 n u
2
1
4
n
n
+
|

\
|
+ .
Ans.: (i)
1 z 4
z 4

(ii)
2
z
1
(iii)
1 z
z
+

(iv)
9 z
z 3
2
+
(v)
4 z
z
2
2
+
(vi)
( ) 1 z z
1
1 z 2
z 2
4 z
z
2

.
Q.No.2.: Find the Z-transforms of f(t)
(i)
4 t 3
e
+
, (ii) t 3 sin , (iii) t 2 cos , (iv) t 3 sin
2
,
(v) t cos
3
, (vi) bt sin e
at
, (vii)
2 t
t . e

.
Z-Transforms: Definitions, Properties Prepared by: Dr. Sunil, NIT Hamirpur (HP) 22
Ans.: (i)
T 3
4
e z
z
. e

, (ii)
1 T 3 cos z 2 z
T 3 sin z
2
+
, (iii)
( )
1 T 2 cos z 2 z
T 2 cos z z
2
+

,
(iv)
( )
(

1 T 6 cos z 2 z
T 6 cos z z
2
1
1 z
z
2
1
2
,
(v)
( ) ( )
(

+
(

1 T 3 cos z 2 z
T cos z z
4
1
1 T cos z 2 z
T cos z z
4
3
2 2
,
(vi)
1 bT cos ze 2 2 z
bt sin ze
aT aT 2 2
eT
+
, (vii).
( )
( )
3
T
T T 2
1 e 2
1 ze ze T

+
.
Q.No.3.: Given ( )
( )
3
2
n
3 z
4 z 3 z 2
u Z

+ +
= , 3 z > , show that u
1
= 2, u
2
= 21, u
3

= 139.
Q.No.4.: Using ( )
( )
2
1 z
z
n Z

= , show that ( )
( )
( )
2
2
2 3
1 cos z 2 z
z 2 cos z z
n cos n Z
+
+
= .
Q.No.5.: Find convolution of
(i) ( )
n
3 * 1 n n , (ii) n cos * 3
n
, (iii)
2
n
sin *
2
n
cos

.
Ans.: (i)
( ) ( ) 3 z 1 z
z 2
2
2

, (ii)
( )
( )( ) 1 cos z 2 z 3 z
cos z z
2
2
+

, (iii).
( )
2
2
3
1 z
z
+
.

*** *** *** *** ***
*** *** ***
***